Hand grip strength and ocular associations: the Ural Eye and Medical Study : clinical science - Bikbov, Mukharram; Zainullin, Rinat M.; Gilmanshin, Timur R.; Iakupova, Ellina M.; Kazakbaeva, Gyulli M.; Panda-Jonas, Songhomitra; Tuliakova, Azaliia M.; Fakhretdinova, Albina A.; Gilemzianova, Leisan I.; Jonas, Jost B. (British journal of ophthalmology, 2023)
Purpose To explore the associations between hand grip strength (HGS) and ocular parameters and diseases. - Design Population-based cohort study. - Methods Participants of the Ural Eye and Medical Study, including 5899 (80.5%) out of 7328 eligible individuals aged 40+ years, underwent systemic and ophthalmological examinations including dynamometric HGS measurement. - Results The study included 5381 (90.4%) individuals (age: 58.6±10.6 years; range: 40-94 years) with HGS measurements. Higher HGS (mean: 30.6±11.7 dekaNewton) correlated (multivariable analysis) with better visual acuity (beta: 0.02, p=0.02), longer ocular axial length (beta: 0.03, p=0.003), higher intraocular pressure (beta: 0.03, p=0.001), thicker peripapillary retinal nerve fibre layer (beta: 0.03, p=0.001) and lower prevalence of diabetic retinopathy (beta: −0.03, p=0.007), after adjusting for younger age, male sex, Russian ethnicity, higher body height and waist to hip ratio, higher educational level, higher physical total score, lower smoking package years, higher serum concentration of haemoglobin, higher prothrombin index, lower leucocyte cell count, lower prevalence of non-alcoholic fatty liver disease, lower depression score and lower prevalence of arthritis. In the model, HGS was not correlated with prevalence of nuclear cataract (p=0.38), cortical cataract (p=0.67), subcapsular posterior cataract (p=0.50), open-angle glaucoma (p=0.22) or angle-closure glaucoma (p=0.27). - Conclusions and relevance In addition to parameters such as lower physical activity, higher depression score and worse general health status, a reduced HGS is associated with visual impairment, shorter axial length, lower intraocular pressure, thinner peripapillary retinal nerve fibre layer and higher prevalence of diabetic retinopathy. HGS dynamometry or a handshake may provide the ophthalmologist additional clinical information about the general health and ocular parameters of the patient.
Erstmals online veröffentlicht: 11. August 2022
Gesehen am 17.06.2024